Infographics powered by SAS data visualization techniques for business reporting - Murphy, Travis (SAS Institute, 2018)
Create compelling business infographics with SAS and familiar office productivity tools. A picture is worth a thousand words, but what if there are a billion words? When analyzing big data, you need a picture that cuts through the noise. This is where infographics come in. Infographics are a representation of information in a graphic format designed to make the data easily understandable. With infographics, you don't need deep knowledge of the data. The infographic combines story telling with data and provides the user with an approachable entry point into business data. Infographics Powered b.